2005
DOI: 10.1126/science.1115360
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis in the Hypothalamus of Adult Mice: Potential Role in Energy Balance

Abstract: Ciliary neurotrophic factor (CNTF) induces weight loss in obese rodents and humans, and for reasons that are not understood, its effects persist after the cessation of treatment. Here we demonstrate that centrally administered CNTF induces cell proliferation in feeding centers of the murine hypothalamus. Many of the newborn cells express neuronal markers and show functional phenotypes relevant for energy-balance control, including a capacity for leptin-induced phosphorylation of signal transducer and activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
706
9
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(756 citation statements)
references
References 38 publications
32
706
9
9
Order By: Relevance
“…β2‐tanycytes have been proposed as a neural stem cell population (Lee et al, 2012) and express Fgf10 (Haan et al, 2013). This potentially influences the birth of new neurons that modulate hypothalamic control of energy balance (Kokoeva et al, 2005; Lee et al, 2012; McNay et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…β2‐tanycytes have been proposed as a neural stem cell population (Lee et al, 2012) and express Fgf10 (Haan et al, 2013). This potentially influences the birth of new neurons that modulate hypothalamic control of energy balance (Kokoeva et al, 2005; Lee et al, 2012; McNay et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…8 Further support for the physiological relevance of hypothalamic neuronal plasticity has come from recent studies using a neuronal growth factor, ciliary neurotrophic factor (CNTF). 9 Kokoeva et al showed that in adult mice, centrally administered CNTF induced cell proliferation in feeding centers of the murine hypothalamus and elimination of cell proliferation by co-administration of a mitotic blocker was associated with a loss of the long-term, but not the short-term, effects of CNTF on body weight. 9 The neurotrophins are a family of growth factors known to be involved in the development, maintenance and function of peripheral and central neurones and may be hypothesized to play an important role in mediating neuronal plasticity in the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…9 Kokoeva et al showed that in adult mice, centrally administered CNTF induced cell proliferation in feeding centers of the murine hypothalamus and elimination of cell proliferation by co-administration of a mitotic blocker was associated with a loss of the long-term, but not the short-term, effects of CNTF on body weight. 9 The neurotrophins are a family of growth factors known to be involved in the development, maintenance and function of peripheral and central neurones and may be hypothesized to play an important role in mediating neuronal plasticity in the hypothalamus. The neurotrophin receptor TrkB and its natural ligand, brain-derived neurotrophic factor (BDNF), have been implicated in the regulation of food intake and body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Other reports indicate that LIF signaling supports the maintenance/ self-renewal of cultured mouse embryonic NSCs (Shimazaki et al, 2001;Pitman et al, 2004;Bonaguidi et al, 2005;Gregg and Weiss, 2005), possibly by activating Notch signaling (Chojnacki et al, 2003). However, little is known about the influence of LIF signaling on NSCs and neurogenesis in vivo: gp130 regulates cellcycle reentry of embryonic cortical progenitors (Hatta et al, 2002), and exogenous CNTF enhances neurogenesis in the adult brain (Emsley and Hagg, 2003;Kokoeva et al, 2005).…”
Section: Introductionmentioning
confidence: 99%